2017
DOI: 10.1021/acs.inorgchem.7b01459
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of the Fleeting Hydroxoiron(III) Complex of the Pentadentate TMC-py Ligand

Abstract: Nonheme mononuclear hydroxoiron(III) species are important intermediates in biological oxidations, but well-characterized examples of synthetic complexes are scarce due to their instability or tendency to form μ-oxodiiron(III) complexes, which are the thermodynamic sink for such chemistry. Herein, we report the successful stabilization and characterization of a mononuclear hydroxoiron(III) complex, [Fe(OH)(TMC-py)] (3; TMC-py = 1-(pyridyl-2'-methyl)-4,8,11-trimethyl-1,4,8,11-tetrazacyclotetradecane), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 89 publications
(161 reference statements)
3
27
0
Order By: Relevance
“…1) 1 H NMR titration by adding H 2 O 2 to a mixture of catalyst H2 1 (1 equiv) and substrate a1 (30 equiv) in CD 3 OD revealed a monotonic decrease of the signals of H2 1 and concomitant formation of cis ‐diol d1 , with H2 1 almost vanishing when circa 3 equiv of H 2 O 2 were added (Figure a). 2) UV/Vis titration by adding H 2 O 2 to a solution of H2 1 in MeOH revealed the appearance of a shoulder band at approximately 350 nm attributable to the LMCT of Fe III species; this band plateaued when circa 3 equiv of H 2 O 2 were added (Figure b). 3) The X‐band EPR spectrum of a mixture of H2 1 and H 2 O 2 (10 equiv) showed new signals with g values at 9.0, 7.0, and 4.3, which can be ascribed to high‐spin S =5/2 Fe III species (Figure c) .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…1) 1 H NMR titration by adding H 2 O 2 to a mixture of catalyst H2 1 (1 equiv) and substrate a1 (30 equiv) in CD 3 OD revealed a monotonic decrease of the signals of H2 1 and concomitant formation of cis ‐diol d1 , with H2 1 almost vanishing when circa 3 equiv of H 2 O 2 were added (Figure a). 2) UV/Vis titration by adding H 2 O 2 to a solution of H2 1 in MeOH revealed the appearance of a shoulder band at approximately 350 nm attributable to the LMCT of Fe III species; this band plateaued when circa 3 equiv of H 2 O 2 were added (Figure b). 3) The X‐band EPR spectrum of a mixture of H2 1 and H 2 O 2 (10 equiv) showed new signals with g values at 9.0, 7.0, and 4.3, which can be ascribed to high‐spin S =5/2 Fe III species (Figure c) .…”
Section: Resultsmentioning
confidence: 98%
“…2) UV/Vis titration by adding H 2 O 2 to a solution of H2 1 in MeOH revealed the appearance of a shoulder band at approximately 350 nm attributable to the LMCT of Fe III species; this band plateaued when circa 3 equiv of H 2 O 2 were added (Figure b). 3) The X‐band EPR spectrum of a mixture of H2 1 and H 2 O 2 (10 equiv) showed new signals with g values at 9.0, 7.0, and 4.3, which can be ascribed to high‐spin S =5/2 Fe III species (Figure c) . In addition, the crude Fe III species, obtained by removing all the volatiles under vacuum, could also catalyze the cis ‐dihydroxylation of a1 with H 2 O 2 to afford d1 in 60 % yield.…”
Section: Resultsmentioning
confidence: 98%
“…[18c] We also examined the catalyst resting state.1 ) 1 HNMR titration by adding H 2 O 2 to amixture of catalyst H2 1 (1 equiv) and substrate a1 (30 equiv) in CD 3 OD revealed amonotonic decrease of the signals of H2 1 and concomitant formation of cis-diol d1,w ith H2 1 almost vanishing when circa 3equiv of H 2 O 2 were added (Figure 3a). 2) UV/Vis titration by adding H 2 O 2 to as olution of H2 1 in MeOH revealed the appearance of as houlder band at approximately 350 nm attributable to the LMCT of Fe III species; [21] this band plateaued when circa 3equiv of H 2 O 2 were added (Figure 3b). 3) TheX-band EPR spectrum of amixture of H2 1 and H 2 O 2 (10 equiv) showed new signals with g values at 9.0, 7.0, and 4.3, which can be ascribed to high-spin S = 5/2 Fe III species (Figure 3c).…”
Section: Angewandte Chemiementioning
confidence: 98%
“…[6] An alternative tool is,f or example,t he analysis of deformation energies,a sproposed by the group of Shaik. [11] Yet DFT does frequently allow for the qualitative,a nd even quantitative,d escription of complex chemical transformations (including reactions involving PCET) [12] and its software implementations have by now reached as tate of maturity allowing for in-depth studies of large (and more importantly, experimentally accessible) systems.A nalysis of stationary points for ac PCET reaction of an Fe III ÀOH complex with TEMPOH [13] prompted us to explore the possibilities of monitoring electron flow in such PCET transformations using the IBO representation, to reveal their reaction mechanisms directly. With modern software and computers it is absolutely possible to determine approximate but qualitatively correct (Kohn-Sham) electronic wave functions for most of the involved species and, based on those,a lso determine all likely intrinsic reaction paths for possible PCET events and compare their barriers.O nce the most favorable reaction path has been determined, it should be possible to simply analyze the obtained trajectory of the ground state Nelectron wave function directly to clarify the concrete nature of the process.A fter all, the N-electron wave function contains all information about the N-electron system which is physically observable.A dditionally,r ecently introduced analytic methods,s uch as the intrinsic bond orbital (IBO) [8] transformation, provide an exact representation of any Kohn-Sham density functional theory (DFT) wavefunction, which is well amenable to the analysis of electronic structure changes in intuitive terms.W ehave previously demonstrated that the changes which IBOs undergo along agiven reaction path can be linked to curly arrows [9] and are indeed suitable for the investigation of C(sp 3 )ÀHa ctivation reactions.…”
mentioning
confidence: 99%
“…[10] These previously investigated reactions were of closed shell nature and only involved the movement of electron pairs.Asaresult, previous investigations did not give rise to the challenges that open shell systems,e specially in homolytic bond cleavage, pose to most computational chemistry methods,a nd in particular to single-reference methods such as DFT. [11] Yet DFT does frequently allow for the qualitative,a nd even quantitative,d escription of complex chemical transformations (including reactions involving PCET) [12] and its software implementations have by now reached as tate of maturity allowing for in-depth studies of large (and more importantly, experimentally accessible) systems.A nalysis of stationary points for ac PCET reaction of an Fe III ÀOH complex with TEMPOH [13] prompted us to explore the possibilities of monitoring electron flow in such PCET transformations using the IBO representation, to reveal their reaction mechanisms directly.…”
mentioning
confidence: 99%